PSYCHIATRIC MANIFESTATIONS OF POST-ORGASMIC ILLNESS SYNDROME: A CASE REPORT - Yousafzai, Abdul Wahab; Khan, Fatima Saeed (Journal of Ayub Medical College Abbottabad, 2025)
Post-orgasmic illness syndrome (POIS) is a rare condition, typically characterized by physical symptoms following ejaculation; however, its psychiatric implications remain underreported. We present a case involving episodic cognitive disturbances, social withdrawal, anhedonia, and persistent suicidal ideation occurring after ejaculation. The patient experienced a significant diagnostic delay, resulting in progressive functional decline. Despite multi-drug therapy and immunotherapy, clinical improvement remained limited. This case highlights the limitations of current diagnostic and therapeutic approaches. There is a pressing need for psychiatric integration in POIS management and the development of culturally informed diagnostic frameworks.